Sanksi Pidana Terhadap Pelaku Tindak Pidana Penganiayaan yang Mengakibatkan Luka Berat - Ngurah Arya Kusuma; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2021)
Legal policy directions aimed at making the law as rules that provide protection for the rights of citizens and ensure the life of the generation in the future. In some countries the legal system in Indonesia varies, its legal system is still less well, in practice the country continues to experience a modernization of the State and no one else who can resist it. Criminal law in Indonesia being one of the very important guidelines in realizing a justice. The book of the law of criminal law (Criminal Code) is a strong basis in order to determine the Act illegal and has strict sanctions for those who break them. Acts of persecution that we've seen from a variety of sources into a sign that it does not escape from a less controlled society behavior be it due to low levels of education and the influence of the environment guidelines for less either. As for the formulation of the problem of how judges in Consideration of case of disconnect and torture that resulted in heavy cuts?, how is the criminal sanction in criminal acts and torture that resulted in severe injuries? The type of research conducted normative legal research. The basic consideration of the judge examines the truth of the case that dealt with advance, because the judges are required to enforce the law and justice, an impartial judge to give consideration in deciding a matter with The Almighty Godhead based and is earnest about things concerning the incriminating and lighten criminal. Criminal sanctions being dropped is imprisonment for 1 (one) year which reduced the period of detention.